TINJAUAN KRIMINOLOGIS TERHADAP TINDAK PIDANA PENCURIAN KERBAU DI WILAYAH HUKUM KEPOLISIAN RESOR SUMBA BARAT - Bole, Lowa; Sogara, Yohanes Umbu; Samara, Finsensius; Rade, Stefanus Don (Justitia et Pax, 2023)
The law can contribute maximally to the implementation of legal development if law enforcement officials and all levels of society are subject to and obey legal norms. However, in reality, not all elements of society obey the existing rules. This has led to the emergence of unlawful acts, such as the crime of buffalo theft. The crime of livestock theft is considered one of the criminal acts that are very detrimental as well as disturbing the community with the modus operandi of the perpetrators of buffalo theft in the West Sumba Resort Police Area with the problem of factors that cause the crime of buffalo theft and its countermeasures. This type of research is empirical legal research, using a sociological approach, namely identifying and conceptualizing law as a real and functional institution in a real-life system, this research was conducted in the West Sumba Resort Police Law Area, East Nusa Tenggara (NTT). Factors that cause the crime of buffalo theft are economic factors, environmental factors, and educational factors. The efforts of the West Sumba Resort Police in tackling the crime of buffalo theft in the West Sumba Resort Police Jurisdiction are through preventive efforts and repressive efforts.